A comparison of mathematical features of Turkish and American textbook definitions regarding special quadrilaterals. Issue 4 (19th May 2019) - Avcu, Ramazan
ABSTRACT: In this study, I analyzed and compared definitions of special quadrilaterals presented in the US and Turkish secondary school mathematics textbooks. To this end, seven textbooks from each country were examined based on the following features of mathematical definitions: form of presentation and mathematical correctness, minimality, the nature of definitions, and the reference sets and geometric properties used in definitions. The results showed that Turkish textbooks include both procedural and structural definitions of quadrilaterals, while procedural definitions are non-existent in the US mathematics textbooks. Meanwhile, all structural definitions and all procedural definitions excluding one are mathematically correct. Besides, in both country textbooks, there exists more number of minimal and inclusive definitions compared to the non-minimal and exclusive ones. Finally, textbooks from both countries mainly use quadrilaterals as reference sets and sides as geometric properties in definitions of special quadrilaterals. The results bring to light the varied opportunities provided to the students by the US and Turkish textbooks to experience and learn definitions of special quadrilaterals.